Namibia : Selected Issues and Statistical Appendix. (IMF Staff Country Reports; Country Report ;, 2008)
The recent uptrend in Namibia's current account surplus reflects an increase in public and private savings. Tighter domestic investment rules will not reduce capital outflows. The phasing and macroeconomic impact of regulatory changes requires careful scrutiny. Market-based incentives for investment repatriation are attractive. Namibia's non-renewable natural resource sector is a significant contributor to Namibia's economy and it is important to continue management of its mineral resources wisely. Faster growth in low-skill job opportunities and more flexible labor market institutions will help tackle unemployment in the short-term.